Analysis of Design and Construction Integration of Rigid Bracing Dome. Issue 11 (November 2015) - Gao, Zhanyuan; Xue, Suduo; He, Yongfa
Rigid bracing dome is a new type of pre-stressed space structure, which of upper part is a cable net system, and the lower part is a rigid rod supporting system. The rigid rods of lower part are high-strength steel tie rods except the brace rods. From the perspective of engineering application, the analysis method and steps of design and construction integration are given, which of key problems are pointed out. The key parameters for determining the geometric shape are span, rise, the sublevel number of radial direction, the subsection number of circumferential direction and nodes coordinates. The parameters shall be determined by the concrete requirements of engineering practice, relevant specifications and high-strength steel tie rod materials. The formula of original cable length is deduced, which of correctness and feasibility is validated by numerical example. A new node of brace rod and method for determining its key parameters are given. The construction method, that is node-by-node assembling and then integral tensioning and lifting, and its concrete installation steps are provided. Simulation analysis is conducted on the construction process with finite element dynamic relaxation (FEDR) method. The research results provide necessary theoretical reference for design and construction of rigid bracing dome.